Efficacy of therapies in the treatment of Guillain-Barre syndrome: A network meta-analysis. Issue 41 (15th October 2021) - Lin, Jingfeng; Gao, Qiang; Xiao, Kang; Tian, Danfeng; Hu, Wenyue; Han, Zhenyun
Abstract: Background: Guillain-Barre syndrome (GBS) is a disease with the features of acuteness, paralysis, inflammation, and in peripheral nerves. There are many current treatment options with varying efficacy, and to assess their effectiveness, we performed a network meta-analysis (NMA). The study protocol was registered at PROSPERO (CRD: 42019119178). Posted history: this manuscript was previously posted to medRxiv: doi: https://doi.org/10.1101/2020.06.03.20121780 . Methods: The literature search database includes Web of Science, PubMed, Embase, and the Cochrane library that meets the requirements. We performed the NMA using controlled trials with 2 kinds of outcomes. We used the gemtc R package to perform the NMA to evaluate different GBS treatments' relative results. The consistency of direct and indirect evidence was also assessed by R software with gemtc package. Results: This NMA study included a total of 2474 subjects from 28 trials with 15 kinds of therapies. No improvement was observed in methylprednisolone and prednisolone compared with placebo. Conversely, plasma exchange (PE) and intravenous immunoglobulin (IVIg) were more effective than placebo. There was no significant difference between different doses and courses of PE and IVIg. For combination treatment, such as IVIg+eculizumab, immunoadsorption followed by IVIg and PE followed by IVIg, they didn't show significant advantages than IVIg and PE in NMA. On the consistency examination between direct and indirect evidence, there was no apparent heterogeneity between them. Funnel plots indicated there was little possibility of publication bias in this study. Conclusion: PE or IVIg has significant efficacy for GBS patients. The effects of several kinds of therapies should be further explored. Corticosteroids have no considerable impact on GBS.